Educational Paradigm Shift of Innovative Society - Kálmán Anikó; Kálmán Botond Géza; Poyda-Nosyk Nina (НДІ ПЗІР НАПрН України, 2022)
The relationship between Industry 4.0 and education is a common research topic these days. Its examination is usually carried out either from the economic side or from the education side. However, this relationship also affects many other areas of life, so it is worth analysing from the perspective of other sciences as well. An outsider’s point of view can draw attention to details that do not stand out from the overall picture for either industry or education researchers the purpose of this study is to draw attention to such points of view. For this purpose, authors examined the questionnaires of the pilot test of older planned research using the method of text analysis. The educational paradigm always, in any historical era, acts as a paradigmatic idea of the development of innovations and the economic development of society as a whole. The trajectory of society’s development and the saturation of the labor market with high-quality specialists will depend on the correct interaction of the subjects of the educational process, including the management of educational institutions and guarantors of educational programs, with employers. Such interaction will influence the formation of the correct system of competencies in future specialists, which must be adapted to new challenges and market needs. Properly chosen communication approaches establish the priority of knowledge, cause the need to improve the quality of this knowledge and understand the consequences of their impact on society and, in particular, on the innovative development of society. Based on the survey results, the transformation of the teacher’s role is one of the most important changes compared to traditional education. However, the renewal of the curriculum and the application of modern methods in education also play a significant role. There is no need to give students instruction manuals, but knowledge and skills that enable them to learn new knowledge. Survey results show that educational paradigm shift can be a result of developing the modern educational content and methods and lead to the qualitative development of innovative society. Взаємозв›язок між Індустрією 4.0 та освітою є поширеною темою досліджень сьогодні. Зазвичай його вивчення здійснюється або з економічного боку, або з боку освіти. Однак цей взаємозв›язок також впливає на багато інших сфер життя, тому варто проаналізувати його і з точки зору інших наук. Погляд зі сторони може привернути увагу до деталей, які не виділяються із загальної картини ні для дослідників галузі, ні для дослідників освіти, і метою цього дослідження є привернення уваги до таких точок зору. Для цього автори проаналізували анкети пілотного тестування старих запланованих досліджень за допомогою методу текстового аналізу. Освітня парадигма завжди в будь-яку історичну епоху виступає парадигмальною ідеєю розвитку інновацій та економічного розвитку суспільства в цілому. Від правильної взаємодії суб›єктів освітнього процесу, зокрема керівництва навчальних закладів та гарантів освітніх програм, з роботодавцями буде залежати траєкторія розвитку суспільства та насичення ринку праці якісними фахівцями. Така взаємодія впливатиме на формування правильної системи компетентностей у майбутніх фахівців, яка має бути адаптована до нових викликів та потреб ринку. Правильно обрані комунікаційні підходи встановлюють пріоритет знань, викликають необхідність підвищення якості цих знань та розуміння наслідків їх впливу на суспільство і, зокрема, на інноваційний розвиток суспільства. Виходячи з результатів опитування, трансформація ролі викладача є однією з найважливіших змін порівняно з традиційною освітою. Однак оновлення навчальної програми та застосування сучасних методів в освіті також відіграють значну роль. Потрібно давати учням не інструкції, а знання та навички, які дозволять їм засвоювати нові знання. Результати опитування показують, що зміна освітньої парадигми може стати результатом розвитку сучасного змісту та методів освіти і призвести до якісного розвитку інноваційного суспільства.
Keywords: education; Industry 4.0; paradigm shift; out-of-the-box; viewpoints; освіта; Індустрія 4.0; зміна парадигми; нестандартність; точки зору